A method for economic input-output social impact analysis with application to U.S. advanced manufacturing. (1st March 2019) - Richter, Justin S.; Mendis, Gamini P.; Nies, Larry; Sutherland, John W.
Abstract: Industrial sustainability performance has, up until recently, been mainly based on a combination of economic and environmental measures. The social dimension of sustainability performance remains largely unknown. The lack of understanding of social performance, i.e., how stakeholder needs are impacted by industrial production, limits the capacity of decision makers to pursue fully informed choices. Fortunately, large quantities of economic and social data exist in the public domain. The vast economic and social data enable the creation of industry-related social impact metrics that can describe how industry directly affects society. However, assessing social impacts in an economy requires a multidisciplinary modeling approach. The proposed method, economic input-output social impact assessment, is developed to integrate economic production with two new social impact metrics based on employee/worker-needs: Cost Of Injuries identifies employee safety/security needs, and Employees below a Living Wage identifies worker basic needs. The model is applied using a case study that introduces the economically important and technologically innovative Advanced Manufacturing cluster of industries in the United States. In 2012, Advanced Manufacturing represented over 39% of U.S. manufacturing output and 7.8%, or $2.25 trillion. of the U.S. total economic output ranking 6th in the total economy. As a result of the model, Advanced Manufacturing was attributed 8.5%, or $1.3 billion, for the total national social impacts of Cost Of Injuries, ranking 5th in the U.S. economy. Advanced Manufacturing was also attributed 3.5%, or 3 million employees, for the total national social impacts of Employees below a Living Wage, ranking 12th out of the 16 economic sectors studied. The economic input-output social impact assessment method is demonstrated to provide a measurable path forward to evaluate the social performance of industries. Highlights: Proposed method establishes a primary link from economic activity to social impacts. Two new social impact metrics proposed to measure industrial social performance. Advanced Manufacturing industrial cluster shown to have high Cost of Injury impacts. Using public data, industrial social performance for the United States economy.